2021
DOI: 10.1111/all.14697
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary consensus on sputum induction biosafety during the COVID‐19 pandemic

Abstract: Inflammatory cell counts from sputum induction (SI) are currently the most effective non-invasive way to assess bronchial inflammation and predict therapeutic responses in patients with asthma. 1,2 However, there is currently a high risk of contagion from patients infected with SARS-CoV-2, 3 since SI involves the generation of aerosols, cough manoeuvres and the handling of samples. There is therefore a need to establish safety protocols for medical procedures performed in routine clinical practice in a return … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Sputum induction is the gold standard approach to the non‐invasive study of airway inflammation. A consensus‐based protocol to ensure its biosafety in clinical practice during the current COVID‐19 pandemic was recently published 131 …”
Section: Asthma and Covid‐19 Pandemicsmentioning
confidence: 99%
“…Sputum induction is the gold standard approach to the non‐invasive study of airway inflammation. A consensus‐based protocol to ensure its biosafety in clinical practice during the current COVID‐19 pandemic was recently published 131 …”
Section: Asthma and Covid‐19 Pandemicsmentioning
confidence: 99%
“…In this case, the medical protocols were adapted to guarantee the safety of the patients and healthcare professionals, such as the use of personal protection equipment, and alternative sampling and processing procedures. 86 EAACI launched a series of statements and position papers providing official recommendations for the treatment of drug hypersensitivity, allergic rhinitis, asthma, and other allergic diseases during the COVID-19 pandemic (Table 1) 14,87,89-92 . It also offered…”
Section: Allergy Care Does Not Stop During Covid-19mentioning
confidence: 99%
“…As sputum induction generates aerosols it presents a high risk of viral transmission. In this case, the medical protocols were adapted to guarantee the safety of the patients and healthcare professionals, such as the use of personal protection equipment, and alternative sampling and processing procedures 86 …”
Section: Allergy Care Does Not Stop During Covid‐19mentioning
confidence: 99%
“…The use of aerosol‐generating procedures such as OAC, spirometry, and IS testing has been restricted due to the risk of virus transmission. As the pandemic was not likely to stop, the authors of guidelines focused on how to safely perform some of these procedures, 17 and an urgent need emerged to develop tools for the diagnosis of aspirin hypersensitivity based on clinical data that are easy to obtain during the pandemic. Recently, it was shown that an informatics algorithm based on electronic health records datasets including inflammatory biomarkers, could successfully identify, with a high positive predictive value, both known and previously undiagnosed cases of NERD 18 .…”
Section: Discussionmentioning
confidence: 99%